PENDIDIKAN AKHLAK DALAM PERSPEKTIF AL-GHAZALI - Moh. Irfan; Khoirul Huda; Zainul Abidin (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2024)
This research aims to describe Moral Education from Al-Ghazali's Perspective. This research is library research using a qualitative descriptive approach. Data collection uses documentation methods, while data analysis uses inductive and deductive analysis. The results of this research show that moral education is the core or peak of all forms of education. This education is actually the goal of the entire existing education system. So the main exemplary factor becomes a very important part of the teaching method.